Condition of Spatial Literacy and Students' Spatial Thinking Ability in Mastering the Use of Maps at State Senior High School - Nurjanah, Nurjanah; Sya, Ahman; Hotimah, Oot; Samadi, Samadi; Herlina, Lina (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
The aim of this research is to determine students' literacy conditions, spatial thinking abilities, and mastery of map use. The research was conducted at SMAN 3 Depok using quantitative research methods. The data collection technique in this study used a questionnaire. The research population was 168 students of class XI SMAN 3 Depok. It is necessary to have sharp research indicators in each aspect of spatial literacy, spatial thinking skills, and mastery of map use, and it is necessary to have in-depth analysis-synthesis related to the interconnectedness of each aspect of map use, spatial literacy, and spatial thinking skills Research Results: SMAN 3 Depok students have a high level of ability in spatial literacy and map use, moderate ability in spatial thinking ability, and mastery of map use. High spatial literacy skills can be the basis for developing spatial thinking skills through map media in geography learning.